Regulatory Compliance: A Crucial Governance Obligation in advancing Accountable Public-Private Partnerships (PPPs) under the AfCFTA Agreement - Cave, Lincoln (Strategic review for southern Africa = Strategiese oorsig vir suider-Africa, 2024)
The African Continental Free Trade Area (AfCFTA), once fully implemented, provides the basis for Public-Private Partnership (PPP) projects to become the most appropriate means to facilitate and contribute to meeting the economic development goals of individual African states. However, the agreement emerges against the backdrop of chronic institutional governance failures in matters of public resource management, which continue to affect the service delivery mandate of governments in developing states. Therefore, any such project needs to guarantee accountable, efficient, effective, and result-driven outcomes. This is to safeguard against such initiatives not depriving citizens of benefitting. The article presents regulatory compliance as a crucial component in the role of private and public entities to assist governments to realise developmental goals through suitable joint venture projects.